Analysis of the Factors Influencing Happiness Among the Employees of the Fashion Retail Industry of Assam - Goswami, Chayanika (Digital Repository of Theses, 2026)
This paper is based on research into the determinants of employee happiness in the Assam fashion retailing sector through the combination of the PERMA Model by Seligman and the Authentic Happiness Theory (AHT). Since it is acknowledged that the state of employee happiness is a strategic driver of productivity, engagement and organizational sustainability, the study constructs a broad theoretical foundation by placing the phenomenon of workplace happiness in the frameworks of modern positive psychology and putting it into perspective with the socio-cultural and operational realities of the retail sector in Assam. An analysis of the available literature shows that there is a substantial gap in the empirical studies, especially with regard to the combined effects between demographic, organizational and psychological variables on happiness in new markets in the retail industry. Quantitative research design was adopted, and stratified random sampling was used to obtain data about 300 employees working in the major retail format. The organized questionnaire based on PERMA and AHT was used and the reliability of the measurement scales could be verified (0.907 AHT; 0.983 PERMA). Statistical tests such as correlation, ANOVA, regression and Tukey HSD were done using SPSS and Excel. Results show that the PERMA model is a powerful predictor of employee happiness (0.863 p < .001) with a variation of 71.1%. Gender and marital status were not found to be significant predictors of ES, whereas income and employment type had a low level of influence. The workplace determinants, such as job satisfaction, payment, work environment, work life balance and administrative practices were also identified to have a meaningful influence on the results of happiness. Based on these observations, the research proposes the PERMA Happiness Retail Happiness Management Framework (PRHMF), a managerial application that connects the psychological well-being and the fundamental retail performance metrics which are sales conversion, retention, customer experience and operational efficiency. The model comprises of diagnostic tools, KPI scorecard and a systematic roadmap of implementation in 90 days. Cost-benefit analysis suggests that there are significant organizational returns that can be approximated at 13-20X ROI, which is based on the lowered attrition rates, increased engagement and sales improvement. The study places the concept of employee happiness as more than an effectual state but a quantifiable and controllable, and economically valuable resource. It provides theoretical input to organizational behavior and practical advice on retail leaders and policymakers seeking to establish sustainable and high-performance working places within the changing retailing environment of Assam.